Analysis of relationship between world crude oil price and inflation in Malaysia / Nawal Afifah Khairuddin - Khairuddin, Nawal Afifah (Faculty of Business and Management, 2010)
Previous researches have been conducted in order to investigate the relationship between crude oil price and inflation rate in the developed and emerging countries in literatures such as Kiseok Lee and Shawn Ni (2001), Ferderer (1996), and Georgio et al. (2007). A study by a significant increase in crude oil price will lead to a substantial rise in production costs hence up warding the pressure on crude oil and also inflation. There are two objectives in this study which are to identify the relationship between crude oil price and inflation and to identify the factors that contribute to fluctuations of oil price. The data of crude oil price and inflation rate range from year 1989 until year 2009, and the data were derived from software named Data Stream and Bank Negara Malaysia. The result of simple regression analysis showed that, there is a negative relationship between the crude oil price and inflation rate.